2022
DOI: 10.3390/diagnostics12020372
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Landscape in Infant High-Grade Gliomas: A Single Center Experience

Abstract: High-grade gliomas (HGG) represent about 15% of all pediatric brain tumors, with a dismal prognosis and survival rates ranging from 15 to 35%. Approximately 10–12% of pediatric HGGs (pHGG) occur in children younger than five years of age at diagnosis, specifically infants (iHGG), with an unexpected overall survival rate (OS) in 60–70% of cases. In the literature, iHGGs include a large variety of heterogeneous lesions with different molecular profiles that likely explain their different outcomes. We report our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Ultimately, 37 articles published between March 1984 and April 12, 2022, reporting on 1387 unique patients were included for data extraction. 15 , 16 , 18 , 19 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 Of the 37 articles, 8 (21.6%) were identified from screening the reference lists of the 29 (78.4%) initially found through the search strategy. 31 , 32 , 36 , 40 , 49 , 56 , 58 , 59 For the IPDMA, 27 articles (73.0%) provided IPD on 427 unique patients (mean [SD] age at diagnosis, 9.3 [5.9] years; 169 of 317 [53.3%] were boys, and 148 were girls [46.7%]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, 37 articles published between March 1984 and April 12, 2022, reporting on 1387 unique patients were included for data extraction. 15 , 16 , 18 , 19 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 Of the 37 articles, 8 (21.6%) were identified from screening the reference lists of the 29 (78.4%) initially found through the search strategy. 31 , 32 , 36 , 40 , 49 , 56 , 58 , 59 For the IPDMA, 27 articles (73.0%) provided IPD on 427 unique patients (mean [SD] age at diagnosis, 9.3 [5.9] years; 169 of 317 [53.3%] were boys, and 148 were girls [46.7%]).…”
Section: Resultsmentioning
confidence: 99%
“… 31 , 32 , 36 , 40 , 49 , 56 , 58 , 59 For the IPDMA, 27 articles (73.0%) provided IPD on 427 unique patients (mean [SD] age at diagnosis, 9.3 [5.9] years; 169 of 317 [53.3%] were boys, and 148 were girls [46.7%]). 18 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 62 Twenty-six articles (70.3%) were observational cohort studies, and 10 (27.0%) were prospective studies. Most of the 36 nonrandomized observational studies (33 [91.7%]) were graded as fair or good quality, and the only RCT was graded as poor quality (eTables 1 and 2 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…However, spinal examples are also reported ( Fig. 6P - Q ) 55 raising the question of whether the inclusion of tumour location within the WHO definition of this entity may be too restrictive.…”
Section: Infant-type Hemispheric Gliomamentioning
confidence: 99%
“…Di Ruscio et al [ 173 ] reported on a study of iHGG patients who received surgery and adjuvant chemotherapy; only two patients received the radiotherapy because their age at their diagnosis was over four-years-old. Molecular investigations, including next-generation sequencing (NGS) and DNA methylation, identified three gene fusions that involve NTRK , one ROS1 fusion, one MN1 rearrangement, and two PATZ1 fusions.…”
Section: The Road To Personalized Medicinementioning
confidence: 99%
“…Molecular investigations, including next-generation sequencing (NGS) and DNA methylation, identified three gene fusions that involve NTRK , one ROS1 fusion, one MN1 rearrangement, and two PATZ1 fusions. According to the molecular results, when the chemotherapy failed to control the disease, the two patients benefited from a target therapy with the NTRK inhibitor larotrectinib, thereby achieving complete remission, an excellent partial response, and no serious side effects [ 173 ].…”
Section: The Road To Personalized Medicinementioning
confidence: 99%